Glucosylceramides containing very long-acyl-chain fatty acid are critical for cotton fiber elongation by influencing brassinosteroid synthesis and signaling - Qiaoling Wang; Xingying Yan; Qi Niu; Hongju Zhang; Huidan Tian; Zheng Chen; Fan Xu; Yu You; Yinghui Gao; Zhiqing Qiao; Ming Luo (Crop Journal)
Sphingolipids are not only a pivotal component of membranes but also act as bioactive molecules. Cotton fiber is one of the longest plant cells and sphingolipids are closely associated with the development of cotton fiber cells. However, their function in cotton fiber cell development and its action mechanism is unclear. Through cotton genetic transformation and chemistry biological approach, we identified the function and action mechanism of the glucosylceramide synthase gene GhGCS1 and its product glucosylceramide (GluCer) in cotton fiber growth. GhGCS1 was preferentially expressed at the stage of fiber elongation and localized in the endoplasmic reticulum. Overexpression of GhGCS1 promoted GluCer synthesis and fiber elongation, which was consistent with the exogenous application of GluCer (FA-C22) (containing very long-acyl-chain fatty acid) to cotton fiber in ovule culture system in vitro. Contrarily, suppressing GhGCS1 expression inhibited GluCer synthesis and fiber elongation, which was similar as the exogenous application of GluCer synthesis inhibitor, PDMP. Transcriptome analysis revealed that the fiber elongation regulated by GhGCS1 was associated with brassinosteroid (BR) synthesis and signaling related gene expression. Meanwhile, we detected the BL content of control and transgenic fiber cells. The BL content significantly increased and decreased in up- and down-regulated transgenic fibers when compared with control fibers, respectively. Furthermore, we found that PDMP treatment blocked BR synthesis and signal transduction, while exogenous application of GluCer could enhance BR synthesis and signaling. Overall, our results revealed that GhGCS1 and GluCer regulated cotton fiber elongation by influencing BR synthesis and signaling. Our study shed a novel insight on regulatory mechanism of cotton fiber elongation and provides theoretical support, genetic resources and novel transgenic materials for improvement of crop quality.